Sensory Profiling and Consumer Preference of Local Bogor Coffee Brands Using CATA (Check-All-That-Apply) Method - Muhammad Fakih Kurniawan; Siti Nursaidah Rahmah; Tiara Amanda Lestari (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Coffee has complex sensory characteristics, such as aroma, flavor, texture, color, and aftertaste. While various local coffee products are available in Bogor, studies on sensory attributes and consumer preferences are limited. This study aimed to evaluate the sensory profiles and preference levels of four local Bogor coffee brands using the CATA method. The samples consisted of commercially available local Bogor coffee products, including robusta-based coffee and an arabica–robusta blend produced by local roasters. A total of 29 sensory attributes were identified through focus group discussions (FGDs) with eight trained panelists and evaluated by 50 general consumers. Hedonic testing was also conducted and analyzed using preference mapping. The results showed that earthy, floral, chocolate, and spicy sensory attributes tended to increase consumer preference, while smoky aroma and rubbery and burned flavors decreased it. Ideal coffee attributes include brown color, fruity flavor, chocolate and spicy aromas, light body, and sour aftertaste. Samples 669 and 614 showed the highest preference cluster (60–80%), while 471 and 628 achieved the lowest (20–40%). These findings demonstrate the importance of sensory attributes in influencing consumer preferences and can serve as a guide for local Bogor coffee producers.